2009
DOI: 10.1177/0734242x09345274
|View full text |Cite
|
Sign up to set email alerts
|

A review of residential solid waste management in the occupied Palestinian Territory: a window for improvement?

Abstract: Solid waste is considered an urgent environmental health issue in the Palestinian Territory. The aim of this paper was to analyse the current status of residential solid waste (RSW) management in the Palestinian Territory, with the objective of identifying windows for improvement. The study is based on a national household sample survey in the Palestinian Territory, which was conducted by the Palestinian Central Bureau of Statistics (PCBS). The results of this study revealed various interesting trends. For exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Solid waste generation rate is reduced when the population of the area increases [14], statistical test revealed that there is a negative moderate correlation between family size and solid waste per capita generation rate (r=-0.449, p value <0.001), this agrees with literature cited by Moftah et al [5]; Turan et al [14]; Boer et al [33]; Yi et al [35]; Al-Khatib and Arafat [36].…”
Section: Samples Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…Solid waste generation rate is reduced when the population of the area increases [14], statistical test revealed that there is a negative moderate correlation between family size and solid waste per capita generation rate (r=-0.449, p value <0.001), this agrees with literature cited by Moftah et al [5]; Turan et al [14]; Boer et al [33]; Yi et al [35]; Al-Khatib and Arafat [36].…”
Section: Samples Analysissupporting
confidence: 87%
“…These results mean that most of Alkalakla municipal solid waste is of organic origin, similar findings are also highlighted in several studies in the literature, showing that waste generated in developing countries contains a large percentage of organic materials World Bank [17]; Sakawi [24]; Al-Khatib and Arafat [36]; Hazra and Goel [38]; Abdul Jalil [39]; Moghadam et al [40]; Moqsud [41]; Lioao et al [42]; and Parrot et al [43]. Different results were obtained by Daura et al [21], they characterized solid waste composition in Kano City and found the percentage of food waste was only (7.49%).…”
Section: Samples Analysissupporting
confidence: 82%
“…Only limited recycling initiatives have been put into practice in the WB region. These initiatives were mostly privately owned and focused mainly on metals, paper, and glass recycling (Al-Khatib and Arafat, 2010a;Al-Khatib et al, 2010b). Recently, SWM has gained significant attention by the Palestinian national authority (PNA) due to its environmental, social and economical implications.…”
Section: Status and Organization Of Swm In Palestinementioning
confidence: 99%
“…Process of the search and selection of documents, n = 7[63][64][65][66][67][68][69], n = 18[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87], n = 10[45,46,61,62,[88][89][90][91][92][93].…”
mentioning
confidence: 99%